Monarchy institution and Sabah political stability - Asmady Idris; Marja Azlima Omar; Rizal Zamani Idris; Suzalie Mohamad; Fauzie Sarjono; Syahruddin Hj Awang Ahmad (ResearchGate, 2024)
Purpose: The main purpose of this article is to analyse the role of Tuan Yang Terutama Yang di-Pertuan Negeri of Sabah, called 'TYT', as representative of Yang di-Pertuan Agong at the state level in ending the political stalemate in Sabah in the three state elections held in 1985, 1994, and 2018 respectively. Theoretical framework: This study applies the conceptual framework of constitutional monarch in relation to the Sabah Constitution on the role of Tuan Yang Terutama Yang di Pertua Negeri of Sabah or with the acronym of TYT (His Excellency the Head of State) in maintaining political stability in the state. Method: Research methods for this study are based on documentary analysis and interviews; Results and conclusion: The study has found that TYT has played an impressive role in maintaining political stability, and ceasing political impasse in Sabah after the three state elections. Research implications: The research implication of this study is to increase the deep knowledge on the role of constitutional monarch, in particular the TYT of Sabah in safeguarding political stability. Originality/value: The study has contributed meaningful political values, especially in analysing the dynamic role of monarch institution in a democratic country like Malaysia.